Development and modern industrial policy in practice : issues and country experiences - Felipe, Jesus (Cheltenham Edward Elgar Publishing Ltd., 2016)
Development and Modern Industrial Policy in Practice provides an up-to-date analysis of industrial policy. Modern industrial policy refers to the set of actions and strategies used to favor the more dynamic sectors of the economy. A key aspect of modern industrial policy is embedding private initiative in a framework of public action to encourage diversification, upgrading, and technological dynamism to achieve development in the twenty-first century. The book reviews key questions that policymakers ask about industrial policy, such as: who selects sectors; what is the rationale for sector selection; what are the main tools to promote sectors; what is the role of human capital; and what are the mechanisms for monitoring and evaluation? Expert contributors discuss how to undertake industrial policy effectively and examine the experiences of Australia, the EU, the Republic of Korea, Malaysia, and the US.
​1. Modern Industrial Policy / Jesus Felipe 2. Issues in Modern Industrial Policy (I): Sector Selection, Who, How and Sector Promotion? / Jesus Felipe and Changyong Rhee -- 3. Issues in Modern Industrial Policy (II): Human Capital and Innovation and Monitoring and Evaluation / Jesus Felipe and Changyong Rhee -- 4. Capability Building and Industrial Diversification / Keun Lee -- 5. Industrial Policy Design and Implementation Challenges / Mushtaq H. Khan -- 6. Catching Up: Structural Transformation and Diversification / Justin Yifu Lin and Yan Wang -- 7. Economic Diversification: Implications for Kazakhstan / Jesus Felipe and Cesar A. Hidalgo -- 8. Industrial Diversification in the People’s Republic of China / Justin Yifu Lin, Cheryl Xiaoning Long and Xiaobo Zhang -- 9. Do as I Say, or As I Do? US Innovation and Industrial Policy since the 1980s / Matthew R. Keller and Fred Block -- 10. The Republic of Korea’s Financial Support for Small and Medium Enterprises and Venture Businesses / Jung-moh Chang -- 11. Industrial Policy: The Australian Experience  / William Francis Mitchell -- 12. Diversification and Industrial Policies in Malaysia / Tham Siew Yean -- 13. Industrial Policy in the European Union / Kristine Farla, Francesca Guadagno and Bart Verspagen-- Index
"Co-publication of the Asian Development Bank and Edward Elgar Publishing."
Includes bibliographical references and index
Keywords: Economic development; ECONOMIC DEVELOPMENT; INDUSTRIAL POLICY